Long non‐coding RNA ESCCAL‐1/miR‐590/LRP6 signaling pathway participates in the progression of esophageal squamous cell carcinoma - Hongya Guan; Pengju Lv; Pengli Han; Lijuan Zhou; Jia Liu; Wei Wu; Ming Yan; Qinghe Xing; Wei Cao (Cancer Medicine, 2023)
Abstract Background Long non‐coding RNAs (lncRNAs) have critical functions within esophageal squamous cell carcinoma (ESCC). However, the function and mechanism underlying ESCC‐associated lncRNA‐1 (ESCCAL‐1) in ESCC tumorigenesis have not been well clarified. Methods ESCCAL‐1, miR‐590 and LRP6 were quantified using qRT‐PCR. Cell viability, migration and invasion abilities were measured using CCK‐8 assay and transwell assays. The protein pression was determined with western blot assay. The xenograft model assays were used to examine the impact of ESCCAL‐1 on tumorigenic effect in vivo. Direct relationships among ESCCAL‐1, miR‐590 and LRP6 were confirmed using dual‐luciferase reporter assays. Results The present work discovered the ESCCAL‐1 up‐regulation within ESCC. Furthermore, ESCCAL‐1 was found to interact with miR‐590 and consequently restrict its expression. Functionally, knocking down ESCCAL‐1 or over‐expressing miR‐590 hindered ESCC cell growth, invasion, and migration in vitro. Moreover, inhibition of miR‐590 could reverse the effect of knockdown of ESCCAL‐1 on cells. Importantly, it was confirmed that LRP6 was miR‐590’s downstream target and LRP6 over‐expression also partly abolished the role of miR‐590 overexpression in ESCC cells. Conclusion We have uncovered a novel regulatory network comprising aberrant interaction of ESCCAL‐1/miR‐590/LRP6 participated in ESCC progression.